Crystal & gem - Symes, R. F.; Harding, R. R. (New York : Knopf : Distributed by Random House, 1991)
Describes how crystals form in nature, how crystals are grown artificially, and how crystals are used in industry. Numerous color photos with text identify the various gemstones.
Includes index.
Keywords: Crystals -- Juvenile literature; Crystallography -- Juvenile literature; Precious stones -- Juvenile literature; Crystals; Crystallography; Precious stones